Effects of milking system on plasmin and plasminogen activity in bovine bulk milk - Höök, Emma (2015)
Protein is an important component in various milk products and has a crucial role in the final quality. Excluding non-protein nitrogen, bovine milk contains about 3.3% protein whereas about 80% of this fraction consists of casein. There are four major members in the casein family: αs1-casein, αs2- casein, β-casein and κ-casein. Proteolytic enzymes are the cause of degradation of the economically important milk proteins. By that, proteases play a more significant role than any other group of enzymes in dairy technology. The proteolytic activity is mainly achieved through activation of the serum protease plasmin. Plasmin alters from its inactive proenzyme, plasminogen and causes a degradation of the protein, such as casein. The aim of this study was to investigate if the type of milking system significantly affected the plasmin and plasminogen activity in bulk milk. Milk from automatic milking system (AMS) was compared with milk from conventional milking system (CMS). The proteolytic enzyme activity was examined by fluorescence measurement. Totally 108 bulk milk samples was included in the study, 52 and 56 from AMS and CMS farms, respectively. In addition to analysis regarding plasmin and plasminogen activity, casein content and milk features such as pH, fat, total protein and SCC were determined. Results showed significantly higher content of αs1-casein in CM milk and αs2- casein was significantly higher in AM milk. Fat and protein were significantly higher in CM milk, meanwhile results regarding pH and SCC showed higher amount in milk derived from AMS. Percentage of proteolytic enzyme activity was significant higher (PL: 17% and PG: 7%) in CMS milk in comparison to AMS milk, suggesting that quality of the protein fraction is better preserved in milk from AMS farms.